Positron Emission Tomography Imaging of [11C]Rosuvastatin Hepatic Concentrations and Hepatobiliary Transport in Humans in the Absence and Presence of Cyclosporin A. Issue 5 (22nd July 2019) - Billington, Sarah; Shoner, Steven; Lee, Scott; Clark‐Snustad, Kindra; Pennington, Matthew; Lewis, David; Muzi, Mark; Rene, Shirley; Lee, Jean; Nguyen, Tot Bui; Kumar, Vineet; Ishida, Kazuya; et al.
Abstract : Using positron emission tomography imaging, we determined the hepatic concentrations and hepatobiliary transport of [ 11 C]rosuvastatin (RSV; i.v. injection) in the absence ( n = 6) and presence ( n = 4 of 6) of cyclosporin A (CsA; i.v. infusion) following a therapeutic dose of unlabeled RSV (5 mg, p.o.) in healthy human volunteers. The sinusoidal uptake, sinusoidal efflux, and biliary efflux clearance (CL; mL/minute) of [ 11 C]RSV, estimated through compartment modeling were 1, 205.6 ± 384.8, 16.2 ± 11.2, and 5.1 ± 1.8, respectively ( n = 6). CsA (blood concentration: 2.77 ± 0.24 μM), an organic‐anion‐transporting polypeptide, Na + ‐taurocholate cotransporting polypeptide, and breast cancer resistance protein inhibitor increased [ 11 C]RSV systemic blood exposure (45%; P < 0.05), reduced its biliary efflux CL (52%; P < 0.05) and hepatic uptake (25%; P > 0.05) but did not affect its distribution into the kidneys. CsA increased plasma concentrations of coproporphyrin I and III and total bilirubin by 297 ± 69%, 384 ± 102%, and 81 ± 39%, respectively ( P < 0.05). These data can be used in the future to verify predictions of hepatic concentrations and hepatobiliary transport of RSV.